PENGUATAN BRANDING BATIK MELALUI PEMASARAN DIGITAL - Doyoharjo, Anggo; Kusumastuti, Dora; Yuliana, Risma (Gapenas Publisher, 2025)
The city of Surakarta has superior batik products that have existed for generations. Batik IKM actors in Surakarta have the potential for quality batik IKM products, but with the rise of online sales of various batik products from other regions, the existence of this IKM batik is experiencing challenges in its marketing. Based on these problems, we carry out community service activities in the form of branding training and assistance to increase the competitiveness of SMEs. Conducting mapping of superior commodities managed by SMEs. Batik SMEs have enormous potential for economic growth and labor absorption. For this reason, supporting facilities and infrastructure for IKM activities must be adequate and efforts are needed to continue to improve the competence of SMEs so that they can increase the competitiveness of SMEs. Conducting access and marketing information for IKM products; Seeing the high potential of internet users in Indonesia, the government must also continue to socialize and coach SMEs in terms of technology utilization, namely through e-Smart SMEs so that more SMEs market their products through marketplaces. The use of e-Smart IKM can be beneficial for both SMEs and the government.